Karakterisasi Metabolit Bioaktif Pare (Momordica charantia) sebagai Pengontrol Gula Darah dan Pendukung Pencernaan - Lisa Fitriana; Ardi Mustakim (Pusat Riset dan Inovasi Nasional, 2026)
Bitter melon (Momordica charantia) is a medicinal plant traditionally used to control blood glucose levels and improve digestive health. These benefits are closely associated with its bioactive metabolite content. This article aims to characterize the bioactive metabolites of bitter melon and to review their potential bioactivity in glycemic control and digestive function. The method employed includes a literature-based characterization of metabolites, identification of major classes of active compounds, and evaluation of analytical techniques commonly applied in natural product research, such as phytochemical screening, chromatography, and spectroscopic analysis. The results indicate that bitter melon contains various bioactive metabolites, including flavonoids, alkaloids, saponins, triterpenoids, and polyphenols, which contribute to blood glucose reduction by enhancing insulin sensitivity and inhibiting glucose absorption. Furthermore, these compounds support digestive health by improving digestive enzyme activity, exhibiting anti-inflammatory effects, and maintaining gut microbial balance. In conclusion, bitter melon represents a promising source of natural bioactive compounds with significant potential for application in health and pharmaceutical development.